Association between ESR1, ESR2, HER2, UGT1A4, and UGT2B7 polymorphisms and breast Cancer in Jordan: a case-control study - AL-Eitan, Laith N.; Rababa’h, Doaa M.; Alghamdi, Mansour A.; Khasawneh, Rame H. (BMC cancer, 2019)
Breast cancer risk, development, and treatment are influenced by genetic variation in certain genes, namely those involved in cell proliferation, tumor suppression, and drug metabolism. In turn, the relevance of the aforementioned genetic variation to cancer depends on the ethnic group in question, highlighting the need for population-specific association studies. Therefore, the objective of the present study was to investigate the association between certain ESR1, ESR2, HER2, UGT1A4, and UGT2B7 single nucleotide polymorphisms and breast cancer. Blood samples were collected from 437 Jordanian-Arab breast cancer patients and healthy volunteers and subject to genotyping using the Sequenom MassARRAY® system (iPLEX GOLD). Our findings show a significant association between breast cancer and the allelic (P = 0.02486879) and genotypic (P = 0.04793066) frequencies of the ESR1 polymorphism rs3798577, a result which was confirmed in different genetic models. No other investigated polymorphism showed a significant association with breast cancer itself in Jordanian Arabs, but the Rare Hz (GG) vs Het (AG) genetic model revealed an association of the disease with the ESR1 polymorphism rs3798577. However, several associations were found between certain polymorphisms and breast cancer's prognostic factors. This study suggests that certain polymorphisms may increase the risk of breast cancer in the Jordanian-Arab population. Future research and clinical translation could incorporate the current results in preventative breast cancer approaches tailored for Jordanian-Arab patients.